The Effect of Learning Vocabulary in Acquisition and Descriptive Text through Hidden Object Games for Junior High School Students (RETAIN, 2023)
In this research entitled "The Effect of Learning Vocabulary in Acquisition and Descriptive Text through Hidden Object Games for Junior High School Students," the aim of this research were to know and explain the implementation, students’ performance, and student’s perception about Hidden Object Game as a digital learning media to learn vocabulary and descriptive text. This research was mix method research. The subjects in this study were 7th grade students in junior high school. This class chose based on the teacher recommendation because in this class’ properties support digital learning activities. The results of this study showed that there were significant differences between students before and after gave treatment. In terms of writing test, the students’ score were improved, especially on vocabulary aspect with percentage 45.7%. The students also gave positive perception towards Hidden Object Game as a digital learning media to learn vocabulary and descriptive text. In conclusion, Hidden Object Game gave positive impact to learn vocabulary in acquisition and descriptive text materials. Keywords: Hidden Object Game, vocabulary, and descriptive text.